Penambahan Natrium Metabisulfit (Na2S2O5) terhadap Vitamin C dan Warna pada Proses Pengeringan Cabai Merah (Capsicum annuum L.) dengan Tunnel Dehydrator - Hisworo Ramdani; Reki Ashadi Wicaksono; Muchammad Agus Fachruddin (JURNAL AGRONIDA, 2018)
The purpose of this study was to investigate the effect of increasing Na2S2O5 towards vitamin C and color red chili (Capsicum annuum L.) dried in dehydration process with tunnel dehydrator.   The research had been performed using factorial randomized design with two factors, i.e.: natrium metabisulfite concentrates (A1 = 0.1%, A2 = 0.2%, and A3 = 0.3%) and soak’s time (B1 = 5 minute, B2 = 10 minute, and B3 = 15 minute).  Parameters analyzed were vitamin C (Jacobs, 1958) and color of red chili dry (Hunter scale).   Natrium metabisulfite concentrated had significant effect on vitamin C (α=0.05), and had no significant effect on color red chili dried.  Soak’s time natrium metabisulfite and the interaction both of them had no significant on vitamin C and color red chili dried. The best treatment of natrium metabisulfite concentrate A1 (concentrate = 0.1%) is the most significant effect.  The best treatment of soak’s time natrium metabsiulfite is B1 (5 minute). The best interactions both of them is A1B1 (concentrate = 0.1% and 5 minute). Keywords: drying process, tunnel dehydrator, capsicum, red chili